Cloning, Characterization and Expression Pattern of the Ovarian Cytochrome P450 Cyp19a1aGene in Gonadal Developmental Period of Cobaltcap Silverside Hypoatherina tsurugae - Dilip Kumar Bej (Journal of BioScience and Biotechnology)
The upregulation of the cyp19a1a transcription factor is required for granulosa cell differentiation and ovarian maintenance. 1630 bp of cyp19a1 mRNA transcript of Hypoatherina tsurugae was cloned and sequenced. It consists of an open reading frame (ORF) of 1551 bp that encodes a 517 aa protein, found to be identical to the sequence of other fish species. A phylogenetic tree was constructed by comparing the mRNA sequence of 41 different fishes across various taxa available in the NCBI database and using an outgroup as Acipenser sinensis. The tree shows a high homology of cyp19a1a from H. tsurugae with cyp19a1a of Maelanotaenia boesemani, the two forming a single clade. The qRT expression of cyp19a1a was studied in both amhy+ (male) and amhy- (female) individuals. In amhy- (female) individuals, the expression was begins from 0 wah and peak at 6 wah then sharply decreases whereas in amhy+ (male) individuals expression was very low and it is in the baseline. The histological sections of gonads were studied in different stages of biweekly collected larvae during the sex determination/differentiation period and it showed that differentiation of gonads male/female was decided at 6 wah. In this stage, the primary oocytes are recognized. These findings add to the knowledge for a better understanding of molecular mechanisms of sex determination and differentiation period in fishes.